Galician and Porcupine Bank Nephrops fishery systems: a comparison from a climate-induced changes perspective - González-Herraiz, Isabel; Fariña-Pérez, Celso; Sampedro-Pastor, Paz; Torres, María de los Ángeles; Cañás, Lucía (ICES, 2009)
Presentación Nephrops norvegicus is a valuable resource of the bottom–demersal ecosystems in the Celtic–Biscay shelf and Iberian coastal large marine areas, of which Porcupine Bank and Galician shelf and upper slope (northwest Spain) are representative, respectively. The catch per unit effort (cpue) of Nephrops fisheries of these areas, considered as an abundance index of populations, decreased in the Porcupine Bank Spanish bottom fishery and dramatically fell in the Galician fishery. The causes for that decline are not known. In this study, the upwelling, North Atlantic Oscillation and Atlantic Multidecadal Oscillation indices series were used as proxies to explore and interpret the variability of the cpue time‐series of the two Nephrops populations from the two areas.